What makes news on the front page? : an investigation of conceptions of newsworthiness in the East African Standard - Nzioka, Roseleen M (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
Determining what is newsworthy is a daily challenge even to the very people who source news, produce and disseminate it. This study is part an exposition and exploration of the different approaches that media researchers have used to explain and determine the value of news. Like similar research before it, this study more specifically delves into the news selection process of news of one particular newspaper with the goal of investigating why and how news is selected for publication in the front page. News is the 'result of many forces: ranging from source power, journalistic orientation, medium-preference and market model, news values and production routines and processes. The study briefly expounds on the different definitions of news as perceived in terms of the developed and developing world. Just as journalists do not operate in a vacuum, a close examination of the various definitions reveals that news cannot be defined in isolation. Its definition is intrinsically tied to that of news values. Also explored here are debates about news values and their Western rootedness. Here reference is made to literature regarding theories on the social construction of meanings and on the gatekeeping concept.The study is informed by similar research in gatekeeping studies and sociology of news studies. It is important to state at the outset that the study is not concerned with how news is produced but why there is a bias for certain kinds of news. I am interested in explaining why and how the writers and editors at the East African Standard make decisions about what is worthy of being published on the front page of the newspaper. This distinction is necessary because the theories that inform this study transcend news sourcing and production. This study takes cognizance ofthe fact that one cannot separate social processes from the individual and vice versa. For this reason, this study investigates and analyses the biases of individual gatekeepers at the East African Standard as well as their collective biases. In the concluding section, this study calls for an alternative paradigm for journalism and news. The foregoing discussions in the other sections prove that a universal definition of news and what is newsworthy will not suffice and there is need to contexualise it.
Keywords: East African Standard (Nairobi, Kenya); Journalism -- Social aspects -- Kenya; Journalism -- Editing -- Kenya; Newspapers -- Sections, columns, etc -- Kenya; Mass media -- Political aspects -- Kenya; Newspapers -- Kenya